Understanding the atomic and electronic structures origin of defect luminescence of CdSe quantum dots in glass matrix. Issue 9 (21st March 2019) - Li, Wenke; Li, Neng; Liu, Chao; Greaves, George Neville; Ong, Wee‐Jun; Zhao, Xiujian
Abstract: Well‐defined density functional theory (DFT) calculations are performed as the first exploratory study for the atomic and electronic mechanism of defect mediated morphology and optical properties of Cdn Sen (n = 3, 10, 13, and 33) quantum dots (QDs) in inorganic amorphous matrix. The intrinsic defects of pristine CdSe QDs, and the interfacial defects between the QDs and surrounding amorphous matrix, were systematically studied. The calculated electronic structure suggested that the pristine CdSe QDs capped by the structural modifiers or non‐bridging oxygen in the amorphous matrix gave rise to the structure reconstruction and paired defect states at the edge of the valence and conduction bands. The orbital analysis elucidated that the redistribution of the majority of HOMO and LUMO electron density was localized over the bonds formed by capping atoms and QDs. These changes in the electronic structures were further demonstrated by CdSe QDs embedded sodium silicate glasses. It turned out that Se atoms at QDs/glass interface were much more active than those found on the surface of organically passivated CdSe QDs. The results serve as a new paradigm in materials research to explore structural origins of defect emission from QDs and a new strategy to develop glasses containing QDs with high photoluminescence quantum efficiency. Abstract : The atomic and electronic structures origin of defect luminescence of CdSe quantum dots in glass matrix was investigated by density functional theory calculation. The simulation results were consistent with the experimental findings.